Significant source of secondary aerosol: formation from gasoline evaporative emissions in the presence of SO2 and NH3 - Chen, Tianzeng; Liu, Yongchun; Ma, Qingxin; Chu, Biwu; Zhang, Peng; Liu, Changgeng; Liu, Jun; He, Hong (Atmospheric chemistry and physics, 2019)
Gasoline evaporative emissions have become an important anthropogenic source of urban atmospheric volatile organic compounds (VOCs) and secondary organic aerosol (SOA). These emissions have a significant impact on regional air quality, especially in China where car ownership is growing rapidly. However, the contribution of evaporative emissions to secondary aerosol (SA) is not clear in an air pollution complex in which a high concentration ofSO2 and NH3 was present. In this study, the effects of SO2 and NH3 on SA formation from unburned gasoline vapor were investigated in a 30 m3 indoor smog chamber. It was found that an increase in SO2 and NH3 concentrations (0–151 and 0–200 ppb, respectively) could linearly promote the formation of SA, which could be enhanced by a factor of 1.6–2.6 and 2.0–2.5, respectively. Sulfate was most sensitive to the SO2 concentration, followed by organic aerosol, which was due not only to the acid catalytic effect, but was also related to the formation of organic sulfur-containing compounds. In the case of an increasing NH3 concentration, ammonium nitrate increased more significantly than organic aerosol, and nitrogen-containing organics were also enhanced, as revealed by the results of positive matrix factorization (PMF) analysis. New particle formation (NPF) and particle size growth were also significantly enhanced in the presence of SO2 and NH3. This work indicates that gasoline evaporative emissions will be a significant source of SA, especially in the presence of high concentrations of SO2 and NH3. Meanwhile, these emissions might also be a potential source of sulfur- and nitrogen-containing organics. Our work provides a scientific basis for the synergistic emission reduction of secondary aerosol precursors, includingNOx, SO2, NH3, and particularly VOCs, to mitigate particulate matter (PM) pollution in China.